Activated carbon adsorbent with high adsorption capacity

By using high adsorption capacity activated carbon adsorbents of metal organic frame materials and secondary activated activated carbon and other components, combined with multi-stage filling method and vibration auxiliary measures, the problems of insufficient adsorption capacity and slow adsorption-desorption speed in the prior art are solved, and more efficient natural gas adsorption and faster adsorption-desorption kinetics are achieved.

CN119549130APending Publication Date: 2025-03-04HUACHUANG MATERIALS (SUZHOU) CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411878857.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The adsorption capacity of the activated carbon adsorbent of the existing natural gas cylinder is not ideal enough, and the adsorption-desorption speed is slow, making it difficult to meet the high flow demand.

Method used

A high-adsorption capacity activated carbon adsorbent consisting of specially treated metal organic frame materials (MOFs), secondary activated activated carbon and composite additives composed of inorganic alkali metal salts and organic amines, and is filled through multi-stage filling method and vibration auxiliary measures.

Benefits of technology

The adsorption capacity of methane is increased by 30-50%, the adsorption amount of impurity gas is reduced by 50-70%, and the adsorption and desorption speed is significantly improved, which can better meet the demand for high-flow gas supply.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses an activated carbon adsorbent with high adsorption capacity, and relates to the technical field of activated carbon adsorbents for natural gas bottles, the activated carbon adsorbent comprises the following components: an active component A: a specially treated metal organic framework material accounting for 10-20% of the total adsorbent material; the active component B is high-quality activated carbon which is subjected to secondary activation treatment and accounts for 60-80% of the total adsorbent material; the auxiliary agent C is a composite auxiliary agent composed of inorganic alkali metal salt and organic amine, the content of the auxiliary agent C accounts for 5-15% of the total adsorbent material, the inorganic alkali metal salt in the auxiliary agent C is potassium carbonate, the organic amine in the auxiliary agent C is triethylamine, and the metal organic framework material in the active component A is MOFs. According to the activated carbon adsorbent with the high adsorption capacity, through the synergistic effect of the active component A, the active component B and the auxiliary C, the methane adsorption capacity can be expected to be improved by 30-50%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of activated carbon adsorbents for natural gas bottles, in particular to an activated carbon adsorbent with high adsorption capacity. Background Art

[0002] At present, activated carbon adsorbents in natural gas bottles have been used to a certain extent in natural gas storage. Traditional activated carbon adsorbents mainly store natural gas through physical adsorption. These activated carbons usually have a large specific surface area and can adsorb natural gas molecules to a certain extent. In the preparation process, common activation methods are mostly used, such as chemical activation (using chemical reagents such as potassium hydroxide, phosphoric acid, etc.) and physical activation (such as water vapor, carbon dioxide activation) to manufacture activated carbon.

[0003] Although the existing activated carbon adsorbents have a large specific surface area, their adsorption capacity for natural gas is still not ideal. Under the same pressure and temperature conditions, the amount of natural gas adsorbed is relatively small, which limits the single filling volume and cruising range of the natural gas cylinder (for application scenarios such as vehicles fueled by natural gas). In addition to methane, the main component of natural gas, some impurity gases such as carbon dioxide and moisture may also be adsorbed. This will not only reduce the effective adsorption of natural gas, but also the presence of impurity gases during the release of natural gas may affect the combustion performance of natural gas. During the filling and use of natural gas, the adsorption-desorption rate of the activated carbon adsorbent is slow. During filling, it takes a long time to achieve a high adsorption amount; during use, the release rate of natural gas cannot meet some application scenarios with high flow requirements, such as the gas supply requirements of high-power natural gas engines. For this reason, we propose an activated carbon adsorbent with high adsorption capacity. Summary of the invention

[0004] In view of the deficiencies of the prior art, the present invention provides an activated carbon adsorbent with high adsorption capacity, which solves the problems raised in the above-mentioned background technology.

[0005] To achieve the above purpose, the present invention is implemented by the following technical scheme: an activated carbon adsorbent with high adsorption capacity, composed of the following components:

[0006] Active component A: A specially treated metal organic framework material, the content of which accounts for 10-20% of the total adsorbent material;

[0007] Active component B: high-quality activated carbon, which has undergone secondary activation treatment, accounting for 60-80% of the total adsorbent material;

[0008] Auxiliary agent C: A composite auxiliary agent composed of an inorganic alkali metal salt and an organic amine, the content of which accounts for 5-15% of the total adsorbent material.

[0009] Furthermore, the inorganic alkali metal salt in the auxiliary agent C is potassium carbonate.

[0010] Furthermore, the organic amine in the auxiliary agent C is triethylamine.

[0011] Furthermore, the metal organic framework material in the active component A is MOFs.

[0012] Furthermore, the pretreatment process is as follows: before filling the natural gas, the natural gas bottle containing the activated carbon adsorbent is first subjected to vacuum treatment to reduce the pressure inside the bottle to below -0.08MPa to remove the air and impurity gases in the bottle.

[0013] Furthermore, the filling method is as follows: adopt a multi-stage filling method, slowly fill natural gas into the bottle at a pressure of 2-3MPa, so that the adsorbent initially adsorbs the natural gas, the process lasts for 5-10 minutes, and gradually increases the pressure, increasing 2-3MPa each time until the target filling pressure is reached.

[0014] Furthermore, the post-processing method is as follows: after filling, the natural gas cylinder is left to stand at room temperature for 10-15 minutes to make the natural gas inside the adsorbent more evenly distributed.

[0015] Furthermore, during the filling process, the natural gas cylinder is vibrated at a frequency of 10-20 Hz to promote the diffusion and adsorption of natural gas molecules in the pores of the adsorbent.

[0016] Furthermore, at each level of pressure in the filling method, a stabilization time of 3 to 5 minutes must be maintained.

[0017] The present invention provides an activated carbon adsorbent with high adsorption capacity, which has the following beneficial effects:

[0018] 1. The high adsorption capacity activated carbon adsorbent is expected to increase the adsorption capacity of methane by 30-50% through the synergistic effect of active component A (metal organic framework material) and active component B (secondary activated carbon) and additive C. This is because the special pore structure of MOFs combined with the high specific surface area of ​​activated carbon, coupled with the regulation of adsorption affinity by the additive, can more effectively adsorb methane molecules.

[0019] 2. This high adsorption capacity activated carbon adsorbent, due to the active component A and the auxiliary agent C have a specific adsorption effect on methane molecules, the adsorption of impurity gases such as carbon dioxide and moisture can be reduced by 50-70%. This helps to improve the purity of natural gas, thereby improving its combustion performance and reducing pollutant emissions during the combustion process.

[0020] 3. During the filling process, the multi-stage filling method and vibration-assisted measures, as well as the optimized structure of the adsorbent itself, make the adsorption rate 40-60% higher than that of traditional adsorbents. During the desorption process, due to the optimization of the adsorption force between the adsorbent and the methane molecules, the desorption rate can also be increased by 30-50%, which can better meet the high-flow gas supply needs. DETAILED DESCRIPTION

[0021] The following examples are used to illustrate the present invention, but they are not intended to limit the scope of the present invention.

[0022] The present invention provides a technical solution: an activated carbon adsorbent with high adsorption capacity, which is composed of the following components: active component A: a specially treated metal organic framework material (MOFs), the content of which accounts for 10-20% of the total adsorbent material, MOFs has a high porosity and an adjustable pore structure, and can provide specific adsorption sites for methane molecules; active component B: high-quality activated carbon, which has been subjected to secondary activation treatment, and accounts for 60-80% of the total adsorbent material. The secondary activation treatment can further increase the specific surface area and the number of micropores of the activated carbon, and select activated carbon with a high specific surface area and a rich pore structure to ensure that a large amount of natural gas can be adsorbed. The larger the specific surface area, the more sites available for the adsorption of natural gas molecules, and the higher the adsorption capacity. The pore size distribution of the activated carbon is optimized so that it contains both micropores suitable for adsorbing methane, the main component of natural gas, and mesopores and macropores that are convenient for gas diffusion. Reasonable pore size distribution can improve adsorption efficiency and adsorption speed. The activated carbon should preferentially adsorb methane, the main component of natural gas, while the adsorption capacity of other impurity gases such as carbon dioxide and nitrogen is relatively weak. This can improve the purity of natural gas and reduce the impact of impurities on the performance of gas cylinders. By surface modification and other treatments on activated carbon, its adsorption selectivity for methane can be enhanced. Activated carbon should have sufficient strength and wear resistance to withstand the pressure, impact and friction that may be encountered during the filling, transportation and use of gas cylinders. Activated carbon with high strength can reduce the risk of breakage and wear, ensure the safety and reliability of gas cylinders, and reasonably control the bulk density of activated carbon so that it can be fully filled in gas cylinders without adding too much weight. Activated carbon with moderate bulk density can increase the storage capacity and energy density of gas cylinders; Auxiliary agent C: a composite auxiliary agent composed of inorganic alkali metal salts and organic amines, such as potassium carbonate and triethylamine, whose content accounts for 5-15% of the total adsorbent material. The auxiliary agent can adjust the surface pH of the adsorbent and enhance the adsorption affinity for methane.

[0023] Pretreatment stage process: Before filling with natural gas, the natural gas cylinder containing activated carbon adsorbent is first subjected to vacuum treatment to reduce the pressure inside the bottle to below -0.08MPa to remove air and impurity gases that may exist in the bottle, creating good initial conditions for the adsorption of natural gas.

[0024] Filling method: Multi-stage filling method is adopted. First, natural gas is slowly filled into the bottle at a relatively low pressure (e.g. 2-3MPa) to allow the adsorbent to initially adsorb natural gas. This process lasts for 5-10 minutes. Then, the pressure is gradually increased by 2-3MPa each time until the target filling pressure (e.g. 20-25MPa) is reached. At each level of pressure, a certain stabilization time (3-5 minutes) must be maintained to ensure that the adsorbent fully adsorbs natural gas. During the filling process, the natural gas bottle is slightly vibrated (vibration frequency is 10-20Hz) to promote the diffusion and adsorption of natural gas molecules in the pores of the adsorbent.

[0025] Post-processing stage: After filling, let the natural gas cylinder stand at room temperature for 10-15 minutes to make the natural gas inside the adsorbent more evenly distributed.

[0026] Adsorption capacity experiment: Under laboratory conditions, the adsorption capacity of the adsorbent for methane was measured by the volume method. The conventional adsorbent and the adsorbent of the present invention were placed in test containers of the same volume, and adsorption experiments were carried out at 25°C and 10MPa. The experimental results show that the adsorption capacity of the conventional adsorbent is 150V / V (volume ratio), while the adsorption capacity of the adsorbent of the present invention reaches 210-225V / V, an increase of about 40-50%, which is consistent with expectations.

[0027] Adsorption selectivity experiment: A mixed gas adsorption experimental device was constructed to simulate the composition ratio in natural gas, in which the methane content was 90%, the carbon dioxide content was 5%, and the water content was 5%. Under the same adsorption conditions, adsorption experiments were carried out on the traditional adsorbent and the adsorbent of the present invention. By analyzing the changes in the content of each component in the mixed gas before and after adsorption, it was found that the adsorption amount of carbon dioxide and water by the traditional adsorbent was 10% and 8% (relative to their initial contents), respectively, while the adsorption amount of carbon dioxide and water by the adsorbent of the present invention was reduced to 3-5% and 2-4%, respectively, with a reduction of 50-70%.

[0028] Adsorption-desorption kinetics experiment: A dynamic adsorption-desorption experimental device was used to measure the adsorption-desorption rate of the adsorbent. In the filling experiment, natural gas was filled into the conventional adsorbent and the adsorbent of the present invention at a pressure of 10 MPa. The results showed that the conventional adsorbent took 30 minutes to reach 90% adsorption, while the adsorbent of the present invention only took 18-20 minutes, and the adsorption rate was increased by about 40%. In the desorption experiment, under the same initial conditions, the conventional adsorbent desorbed 50% of the natural gas within 10 minutes, while the adsorbent of the present invention could desorb 65-70% of the natural gas within 10 minutes, and the desorption rate was increased by 30-50%.

[0029] The following conclusions were drawn from the above experiments:

[0030] Significantly improved adsorption capacity: Through the synergistic effect of active component A (metal organic framework material) and active component B (secondary activated carbon) and additive C, the adsorption capacity of methane is expected to increase by 30-50%. This is because the special pore structure of MOFs combined with the high specific surface area of ​​activated carbon, coupled with the regulation of adsorption affinity by the additive, can more effectively adsorb methane molecules.

[0031] Enhanced adsorption selectivity: Since active component A and additive C have a specific adsorption effect on methane molecules, the adsorption of impurity gases such as carbon dioxide and moisture can be reduced by 50-70%. This helps to improve the purity of natural gas, thereby improving its combustion performance and reducing pollutant emissions during the combustion process.

[0032] Improved adsorption-desorption kinetics: During the filling process, the multi-stage filling method and vibration-assisted measures, as well as the optimized structure of the adsorbent itself, make the adsorption rate 40-60% higher than that of traditional adsorbents. During the desorption process, due to the optimization of the adsorption force between the adsorbent and the methane molecules, the desorption rate can also be increased by 30-50%, which can better meet the high-flow gas supply needs.

[0033] The activated carbon adsorbent of the present application can be used for compressed natural gas (CNG) bottles for automobiles. In the automotive field, with the improvement of environmental protection requirements and the demand for clean energy, the market for natural gas vehicles is gradually expanding. This new activated carbon adsorbent can improve the gas storage capacity of automobile CNG bottles, reduce the number of filling times, and increase the cruising range of the car. A CNG car using traditional activated carbon adsorbent has a cruising range of 300 kilometers. After replacing it with a CNG bottle using the adsorbent of the present invention, after actual testing, under the same natural gas bottle volume and filling pressure, the cruising range can be increased to 350-380 kilometers.

[0034] Application in natural gas storage tanks: For small natural gas storage tanks, such as household natural gas storage tanks or small industrial natural gas storage tanks, the use of this new adsorbent can increase the storage density of natural gas and reduce the volume and cost of the storage tanks.

[0035] The embodiments of the present invention are given for the purpose of illustration and description, and are not intended to be exhaustive or to limit the invention to the disclosed forms. Many modifications and variations will be apparent to those of ordinary skill in the art. The embodiments are selected and described in order to better illustrate the principles and practical applications of the present invention and to enable those of ordinary skill in the art to understand the present invention and thereby design various embodiments with various modifications suitable for specific uses.

Claims

1. An activated carbon adsorbent with high adsorption capacity, characterized in that: It is composed of the following ingredients: Active component A: A specially treated metal organic framework material, the content of which accounts for 10-20% of the total adsorbent material; Active component B: high-quality activated carbon, which has undergone secondary activation treatment, accounting for 60-80% of the total adsorbent material; Auxiliary agent C: A composite auxiliary agent composed of an inorganic alkali metal salt and an organic amine, the content of which accounts for 5-15% of the total adsorbent material.

2. The activated carbon adsorbent with high adsorption capacity according to claim 1, characterized in that: The inorganic alkali metal salt in the additive C is potassium carbonate.

3. The activated carbon adsorbent with high adsorption capacity according to claim 1, characterized in that: The organic amine in the auxiliary agent C is triethylamine.

4. The activated carbon adsorbent with high adsorption capacity according to claim 1, characterized in that: The metal organic framework material in the active component A is MOFs.

5. The activated carbon adsorbent with high adsorption capacity according to claim 1, characterized in that: The pretreatment process is as follows: before filling with natural gas, the natural gas cylinder containing activated carbon adsorbent is first subjected to vacuum treatment to reduce the pressure inside the bottle to below -0.08MPa to remove the air and impurity gases in the bottle.

6. The activated carbon adsorbent with high adsorption capacity according to claim 1, characterized in that: The filling method is as follows: adopt a multi-stage filling method, slowly fill natural gas into the bottle at a pressure of 2-3MPa, so that the adsorbent initially adsorbs the natural gas. The process lasts for 5-10 minutes, and the pressure is gradually increased by 2-3MPa each time until the target filling pressure is reached.

7. The activated carbon adsorbent with high adsorption capacity according to claim 6, characterized in that: The subsequent processing method is as follows: after filling, let the natural gas cylinder stand at room temperature for 10-15 minutes to make the natural gas inside the adsorbent more evenly distributed.

8. The activated carbon adsorbent with high adsorption capacity according to claim 6, characterized in that: During the filling process, the natural gas cylinder is vibrated at a frequency of 10-20 Hz to promote the diffusion and adsorption of natural gas molecules in the pores of the adsorbent.

9. The activated carbon adsorbent with high adsorption capacity according to claim 6, characterized in that: During the filling process, a stabilization time of 3-5 minutes must be maintained at each level of pressure.

Citation Information

Cited By

  • Preparation method of normal-temperature normal-pressure efficient gas adsorption composite material

    CN120860998A